2007
DOI: 10.1021/ie070825i
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Deposition of Titanium Dioxide on Acrylic for Photocatalytic Application

Abstract: Nanoscale TiO 2 was dispersed in a solution of dichloromethane and methanol for deposition on the surface of acrylic sheets. After evaporation of the solvent, the TiO 2 was adhered firmly to the acrylic surface. This deposition method yielded uniform, high surface area coatings as evidenced by scanning electron micrographs. The TiO 2 films deposited on acrylic in this manner have superior durability when compared to TiO 2 deposited on glass supports. The TiO 2 fused on the acrylic surface manifests a comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Immobilising the photocatalyst particles on solid supports such as glass, ceramics, polymers, zeolites, sand, etc. has been widely investigated and has successfully enabled easy separation of the photocatalyst [66][67][68][69][70][71]. However, in the process of attaining easy separation, the photocatalytic activity of the immobilised semiconductors decreased remarkably.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilising the photocatalyst particles on solid supports such as glass, ceramics, polymers, zeolites, sand, etc. has been widely investigated and has successfully enabled easy separation of the photocatalyst [66][67][68][69][70][71]. However, in the process of attaining easy separation, the photocatalytic activity of the immobilised semiconductors decreased remarkably.…”
Section: Introductionmentioning
confidence: 99%
“…A more practical approach is to deposit the photocatalyst on a fixed surface, such as glass (Sobczyń ski & Dobosz 2001), acrylic (Carlson et al 2007) or PET (Meichtry et al 2007) prior to use. This approach eliminates the need for post-irradiation treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Titania is activated by the absorption of UV light (lo400 nm), generating excited electron-hole pairs which drive redox reactions in aqueous media. Degussa P-25 is widely considered to be the benchmark titania photocatalyst and is 80% anatase and 20% rutile, with an average particle size of 30 nm (Carlson et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, acrylic material is a viable alternative to PET for SODIS bottles. In fact, Carlson et al 37 previously reported that the P25 coatings on acrylic showed greater durability and comparable UV photocatalytic degradation of methyl orange to P25 coatings on glass. In a significant field study, Gelover et al…”
mentioning
confidence: 99%